The realization of the word in church cathechism - Venter, C. J. H. (Koers, 1988)
The issue that is investigated concerns the dynamic realization processes which occur on the basis of the preaching of the Word of God in church catechism. The study is undertaken by means of a survey and evaluation of relevant data from Dutch, German, American and South African literature. Following that, with the Bible as the primary source, data with regard to the realization of the Bible in the concrete life of the congregation are surveyed and collated. From the analysis of relevant Biblical data the conclusion is reached that the realization, the making real, of the Word in everyday life and existence follows on the act of preaching. This brings us to the awareness that catechetical teaching (that is, preaching of the Word) should not stop at the dissemination of knowledge only, but the child should be guided to realise the Word in practical terms in everyday life. Lastly, attention is directed to methods of catechetical teaching, to demands for the construction of the lesson and to the person and the actions of the catechist, and how all these combine to serve the child in the process of realization of the Word in his life.